Post Truth: Ethics and Digital Security - Surahman, Sigit; Novrian, Novrian (Siber Journal of Advanced Multidisciplinary, 2024)
In an increasingly advanced digital era, the phenomenon of "post-truth" has become a major concern in the study of digital ethics and security. This article explores the impact of the emergence of post-truth on morality and security in the digital realm. The research method used is literature analysis to investigate how post-truth affects online behavior, alters the dynamics of information, and increases vulnerability to cyberattacks. Additionally, this article introduces several ethical strategies and principles that can be applied to address these challenges, including enhancing digital literacy, implementing stricter regulations, and promoting better understanding of the consequences of spreading false information. Thus, this article illustrates the importance of integrating ethics and digital security as crucial steps towards a more responsible and secure digital ecosystem.